Periodontal disease treatment and risk of preterm birth: a systematic review and meta-analysis Tratamento de doença periodontal e risco de parto prematuro: revisão sistemática e metanálise - Maria Inês da Rosa; Patrícia Duarte Simões Pires; Lidia Rosi Medeiros; Maria Isabel Edelweiss; Jeovany Martínez-Mesa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
The events leading to preterm birth are still not completely understood. A quantitative systematic review was performed to estimate the effects of periodontal care during pregnancy on preventing preterm birth and low birth weight. The meta-analysis included randomized trials with pregnant women with a diagnosis of periodontal disease before 20 weeks of gestation. Relative risk (RR) with 95% confidence intervals (95%CI) was calculated. We evaluated the reduction in preterm and low birth weight. Thirteen trials were included, comparing 3,576 women in intervention groups with 3,412 women receiving usual care. The meta-analysis of the effects of periodontal disease treatment during pregnancy indicated a non-significant reduction in preterm births (RR = 0.90; 95%CI: 0.68-1.19) and low birth weights (RR = 0.92; 95%CI: 0.71-1.20). The creation and examination of a funnel plot revealed clear evidence of publication bias. In summary, primary periodontal care during pregnancy cannot be considered an efficient way of reducing the incidence of preterm birth. Os eventos que levam à prematuridade ainda não são completamente compreendidos. Foi realizada uma revisão sistemática quantitativa para avaliar os efeitos do tratamento de doença periodontal durante a gravidez para prevenir o nascimento prematuro e baixo peso ao nascer. A metanálise incluiu estudos randomizados de grávidas com diagnóstico de doença periodontal antes de 20 semanas de gestação. O risco relativo (RR) com intervalos de 95% de confiança (IC95%) foi calculado. Avaliou-se os desfechos prematuridade e baixo peso ao nascer. Foram incluídos 13 estudos, comparando 3.576 mulheres em grupos de intervenção com 3.412 mulheres que receberam tratamento habitual. A metanálise mostrou uma redução não significativa nos partos prematuros (RR = 0,90; IC95%: 0,68-1,19) e baixo peso ao nascer (RR = 0,92; IC95%: 0,71-1,20). O gráfico de funil revelou clara evidência de viés de publicação. Em resumo, o tratamento periodontal em mulheres grávidas não pode ser considerado uma forma eficiente de reduzir a incidência de parto prematuro ou baixo peso ao nascer.